Second language task-based performance theory, research, assessment - Skehan, Peter (Second language acquisition research series, 2018)
"Second Language Task-Based Performance is the first book to synthesize Peter Skehan's theoretical and empirical contributions in one place. Exploring three distinct themes in each section (theory, empirical studies, and assessment), this influential body of work is organized in such a way that it provides an updated reflection on the material and makes it relevant to today's researchers. In each section, an early publication is matched by at least one later publication, followed by a newly written commentary chapter, the combination of which provides the important function of offering a wider-ranging discussion. This book is an invaluable resource for researchers interested in second language task-based research or second language acquisition more generally"--Provided by publisher.